European corporate governance reform and the German party paradox - Martin Höpner (Max-Planck-Institut für Gesellschaftsforschung, 2003)
This paper addresses the current discussion on links between party politics and production regimes. Why do German Social Democrats opt for more corporate governance liberalization than the CDU although, in terms of the distributional outcomes of such reforms, one would expect the situation to be reversed? I divide my analysis into three stages. First, I use the European Parliament's crucial vote on the European takeover directive in July 2001 as a test case to show that the left-right dimension does indeed matter in corporate governance reform, beside cross-class and cross-party nation-based interests. In a second step, by analyzing the party positions in the main German corporate governance reforms in the 1990s, I show that the SPD and the CDU behave 'paradoxically' in the sense that the SPD favored more corporate governance liberalization than the CDU, which protected the institutions of 'Rhenish,' 'organized' capitalism. This constellation occurred in the discussions on company disclosure, management accountability, the power of banks, network dissolution, and takeover regulation. Third, I offer two explanations for the paradoxical party behavior. The first explanation concerns the historical conversion of ideas. I show that trade unions and Social Democrats favored a high degree of capital organization in the Weimar Republic, but this ideological position was driven in new directions at two watersheds: one in the late 1940s, the other in the late 1950s. My second explanation lies in the importance of conflicts over managerial control, in which both employees and minority shareholders oppose managers, and in which increased shareholder power strengthens the position of works councils. – – Dieses Papier behandelt den Einfluss von Parteien auf die Verfasstheit von Produktionsregimen. Warum steht die SPD für mehr Liberalisierung der Unternehmenskontrolle als die CDU, obwohl man wegen der Verteilungswirkungen solcher Reformen eigentlich das Gegenteil erwarten sollte? Die Argumentation gliedert sich in drei Schritte. Zunächst wird anhand der Kampfabstimmung im Europaparlament über die Übernahmerichtlinie im Juli 2001 gezeigt, dass diesem Konfliktfeld tatsächlich eine Links-Rechts-Dimension zu Grunde liegt - neben einer zweiten, klassen- und parteienübergreifenden Konfliktlinie, die zwischen den Mitgliedsstaaten verläuft. In einem zweiten Schritt wird dargelegt, dass sich SPD und CDU bei den entscheidenden Reformvorhaben der Unternehmenskontrolle in den Neunzigern in 'paradoxer' Weise gegenüberstanden: Während sich die SPD liberalisierungsfreudig zeigte, beschützte die CDU die Institutionen des rheinischen, organisierten Kapitalismus. Das gilt für die Debatten über Transparenz, die Rechenschaftspflicht der Unternehmensleitungen gegenüber den Aufsichtsräten, das deutsche Unternehmensnetzwerk, die Macht der Banken und die Übernahmeregulierung. In einem dritten Schritt werden zwei Erklärungen für diese 'paradoxe' Konstellation angeboten. Die erste Erklärung betrifft den Wandel linker Ideen. In der Weimarer Republik hatten SPD und Gewerkschaftsbewegung ein positives Verhältnis zum organisierten Kapitalismus. Nach dem Zweiten Weltkrieg, in den vierziger und fünfziger Jahren, wurde linkes Ideengut in neue Bahnen gelenkt. Die zweite Erklärung betrifft die Bedeutung von Konflikten über Managerherrschaft. Für diesen Konflikttyp gilt, dass Arbeitnehmer und Minderheitsaktionäre implizite Koalitionen gegen das Management bilden und steigende Aktionärsmacht die Mitbestimmung stärkt.
Keywords: 300